Diabetes mellitus in children - Sperling, Mark A (Saunders, 2005)
Univ. of Pittsburg, PA. Topics include the classification of diabetes mellitus; type 1 diabetes mellitus; type 2 diabetes mellitus in youth; pediatric diabetic ketoacidosis and hyperglycemic hypersmolar state; monogenic and other unusual causes of diabetes; and more. For pediatricians and researchers.
Pediatric clinics of North America, ISSN 0031-3955 vol. 52, no. 6, December 2005
Keywords: diabetes mellitus; Diabetes Complications; pediatrie; diabetologie; dítě; Diabetes Mellitus; diabetes mellitus 1. typu; Child; Diabetes Mellitus, Type 1; komplikace diabetu